Complicated popliteal aneurysms - Mazza, Milton E; Delgado, Bolívar; Sabah, Víctor (Cirugía del Uruguay, 1973)
Case material consists of three patients with complicated popliteal aneurysms. In two of these there was acute massive intramuscular thrombosis, in the third there was embolism, distal to the aneurysm. I'hese complications are discussed, with stress of seriousr.ess of disease and on importance of restoring blood flow towards limb by resorting to modern direct vascular surgery techniques.